The Dynamic Interplay between Appraisal and Core Affect in Daily Life - Kuppens, Peter; Champagne, Dominique; Tuerlinckx, Francis (Frontiers in Psychology, 2012)
Appraisals and core affect are both considered central to the experience of emotion. In this study we examine the bidirectional relationships between these two components of emotional experience by examining how core affect changes following how people appraise events and how appraisals in turn change following how they feel in daily life. In an experience sampling study, participants recorded their core affect and appraisals of ongoing events; data were analyzed using cross-lagged multilevel modeling. Valence-appraisal relationships were found to be characterized by congruency: The same appraisals that were associated with a change in pleasure-displeasure (motivational congruency, other-agency, coping potential, and future expectancy), changed themselves as a function of pleasure-displeasure. In turn, mainly secondary appraisals of who is responsible and how one is able to cope with events were associated with changes in arousal, which itself is followed by changes in the future appraised relevance of events. These results integrate core affect and appraisal approaches to emotion by demonstrating the dynamic interplay of how appraisals are followed by changes in core affect which in turn change our basis for judging future events.